Sleep duration of 24 h is associated with birth weight in nulli- but not multiparous women - Franco-Sena, AB; Kahn, LG; Farias, DR; Ferreira, AA; Eshriqui, I; Figueiredo, ACC; Factor-Litvak, P; Schlüssel, MM; Kac, G (Elsevier, 2018)
Objective This study aimed to evaluate the association between nightly, napping, and 24-h sleep duration throughout pregnancy and birth weight z-score among nulli- and multiparous women. Methods Nightly,napping, and 24-h sleep duration and birth weight z-score (calculated on thebasis of the International Fetal and Newborn Growth Consortium for the 21st century standards) were studied in a cohort of 176 pregnant women from Brazil. Linear mixed-effect analyses were performed to assess the longitudinal evolution of sleep duration and the best unbiased linear predictors of the random coefficients were estimated. The best unbiased linear predictor estimates of sleep duration intercept and slope were included in the linear regression models with birth weight z-score as the outcome. Results The mean hours of nightly sleep decreased during pregnancy in nulliparous women (β = −0.55; 95% confidence interval [CI], −0.83 to −0.27) but the decrease was not statistically significant in multiparous women (β = −0.19; 95% CI, −0.30 to 0.01). Twenty-four hour sleep duration decreased during pregnancy in both multiparous (β = −0.50; 95% CI, −0.76 to −0.25) and nulliparous women (β = 0.77; 95% CI, −1.06 to −0.48). Napping sleep duration did not change in either group. Among the nulliparous women, both first-trimester 24-h sleep duration and its change throughout pregnancy were inversely associated with birth weight (β = −0.44; 95% CI, −0.68 to −0.21; β = −1.75; 95% CI, −3.17 to −0.30, respectively). No associations were detected in multiparous women for nightly and napping sleep duration. Conclusions Nulliparous women with greater decreases in sleep duration throughout their pregnancy gave birth to newborns with lower birth weight z-scores.